The Impact of Economic Digitalization on Regional Economic Convergence in Indonesia - Dwipa, I Dewa Made Agus Arsana (Seminar Nasional Official Statistics, 2025)
Regional economic convergence refers to the tendency to reduce development disparities across regions. This study examines the impact of economic digitalization on regional convergence in Indonesia amid post-pandemic digital acceleration. Using SAKERNAS data, digitalization is measured to address gaps in understanding its varied effects. Employing β-convergence panel regression framework, the study compares model robustness using Ordinary Least Squares (OLS), Robust Standard Errors, and Generalized Least Squares (GLS). The findings reveal that while economic digitalization significantly contributes to growth, it does not sufficiently drive convergence without the interaction of labor and capital factors. These results underscore the necessity of context-sensitive digitalization strategies aligned with regional economic structures to promote inclusive and equitable development.